El Proceso de la Lectura para Desarrollar la Comprensión Lectora en los niños de cuarto año de Educación Básica de la Escuela “García Moreno”, Parroquia Yaruquíes, Cantón Riobamba, provincia de Chimborazo. Periodo lectivo 2014 – 2015 - Auquilla López, Gloria del Carmen (2017)
The present project emerged from a problem detected in the fourth year of basic education at the "Garcia Moreno" School, located in Yaruquies. These children have problems to understand a text, because they expect that the teacher explains the questionnaires, summaries, compositions and assessments; they also have difficulties to read and re-read questions, to employ a new vocabulary, to identify main ideas and establish opinions. Children show little reading comprehension because parents at home do not stimulate reading; that is why the purpose was to determine how the reading process develops the reading comprehension in children, its importance, characteristics and processes of reading comprehension through a research work. The theoretical aspects that support the investigation are framed in the dependent and independent variables such as reading comprehension and the reading process, the research project is supported and based on a documentary and descriptive field review, it is oriented to determine how the qualities are manifested, dimensions or components of the problem; also is based on non-experimental research since it allowed us to observe the subjects of the study in their natural environment to be analyzed. For the collection of information, the observation sheets were used to determine the achievements of twenty four students, concluding that the reading process is very important for reading comprehension, therefore parents should be involved in the whole educational process to form the complete trilogy in education: parents, teachers and students should work in coordinately from their own space.